2002
DOI: 10.1001/archinte.162.22.2545
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Hepatitis C Virus in Human Immunodeficiency Virus–Infected Patients

Abstract: Combination therapy for moderate hepatitis in coinfected patients will increase quality-adjusted life expectancy and have a cost-effectiveness ratio comparable to that of other well-accepted clinical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 160 publications
(144 reference statements)
2
57
0
1
Order By: Relevance
“…A second full paper was identified on searching the references of the included study, and this study met the inclusion criteria. Therefore, two full economic evaluations 64,65 met the inclusion criteria for the review. The study characteristics are presented in Table 9.…”
Section: Quantity and Quality Of The Research Availablementioning
confidence: 99%
See 2 more Smart Citations
“…A second full paper was identified on searching the references of the included study, and this study met the inclusion criteria. Therefore, two full economic evaluations 64,65 met the inclusion criteria for the review. The study characteristics are presented in Table 9.…”
Section: Quantity and Quality Of The Research Availablementioning
confidence: 99%
“…An additional interferon alfa monotherapy arm was included in the Kuehne and colleagues study. 64 Kuehne and colleagues 64 present a cost-utility analysis, while in the more recent Campos and colleagues paper 65 a cost-effectiveness analysis is reported.…”
Section: Quantity and Quality Of The Research Availablementioning
confidence: 99%
See 1 more Smart Citation
“…Kuehne et al demonstrated that combination therapy for histologically moderate HCV in co-infected patients resulted in an increase in quality-adjusted life expectancy while incurring costs comparable with other wellaccepted clinical interventions. 16 However, this analysis was performed before randomized controlled trials had established approximate treatment efficacy rates in HIV-HCV co-infected patients, and the APRICOT trial rates of sustained virologic response were generally lower than the lower bounds of the sensitivity analysis performed by Kuehne and colleagues. Since this prior cost-effectiveness analysis was conducted, considerable progress has been made in discerning treatment efficacy rates and relative risk estimates for progression of liver disease in HIV-HCV co-infected patients.…”
mentioning
confidence: 99%
“…Os critérios considera- Hepatite crônica para cirrose compensada 0,073 0,037-0,146 Kuehne et al 30 Hepatite crônica para hepatocarcinoma 0,001 0,0005-0,0017 Kuehne et al 30 ; El Saadany et al 31 Cirrose para ascite 0,025 0,012-0,05 Vianna et al 14 ; Bennett et al 32 Ascite para ascite refratário 0,067 0,034-0,14 Vianna et al 14 Cirrose compensada para encefalopatia hepática 0,004 0,002-0,008 Bennett et al 32 ; Goulart 33 Cirrose para hepatocarcinoma 0,015 0,01-0,07 Kuehne et al 30 ; Goulart 33 Cirrose compensada para hemorragia gastrointestinal 0,011 0,005-0,02 Vianna et al 14 ; Bennett et al 32 Morte encefalopatia hepática no primeiro ano 0,680 0,34-0,90 Bennett et al 32 Morte encefalopatia hepática anos subsequentes 0,400 0,2-0, Morte associada à espera por transplante 0,102 0,05-0,20 Vianna et al 14 ; Fink et al 34 Figura 1…”
Section: Métodosunclassified